Flow Injection- Spectrophotometric Determination of Vancomycin Hydrochloride in Pharmaceutical Preparations Using Diazotized Metoclopramide - Al-Abachi, Mouyed Q; Hadi, Hind; Yousef, Fadi J (Al-Nahrain Journal of Science, 2018)
A batch and flow injection analysis (FIA) spectrophotometric methods have been developed for the determination of vancomycin hydrochloride (VHC) in aqueous solution and in pharmaceutical preparations. The methods are based on the reaction of VHC with diazotized metoclopramide (DMCP) in alkaline medium. The water soluble yellowish-orange color product was measured at λmax 451 nm. Linearity was observed from 0.5 to 100 and 1 to 550 µg mL−1 of VHC with detection limits of 0.230 and 0.419 µg mL−1 by batch and FIA procedure respectively. The sampling rate was 128 injections per hour for flow injection methods. The effects of chemical and physical parameters have been carefully considered and the proposed procedures were successfully applied to the determination of VHC in pharmaceutical formulations.